2012
DOI: 10.1038/ismej.2012.47
|View full text |Cite
|
Sign up to set email alerts
|

Salt marsh sediment diversity: a test of the variability of the rare biosphere among environmental replicates

Abstract: Much of the phylogenetic diversity in microbial systems arises from rare taxa that comprise the long tail of taxon rank distribution curves. This vast diversity presents a challenge to testing hypotheses about the effects of perturbations on microbial community composition because variability of rare taxa among environmental replicates may be sufficiently large that it would require a prohibitive degree of sequencing to discern differences between samples. In this study we used pyrosequencing of 16S rRNA tags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 33 publications
9
55
0
Order By: Relevance
“…In previous studies (Horner-Devine et al, 2004; Có rdova-Kreylos et al, 2011), salt marsh inhabiting bacterial communities were described at deep sequencing resolution (Bowen et al, 2012) and at continental scales (Martiny et al, 2011). Moreover, their response to external nutrients has been recorded (Bowen et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies (Horner-Devine et al, 2004; Có rdova-Kreylos et al, 2011), salt marsh inhabiting bacterial communities were described at deep sequencing resolution (Bowen et al, 2012) and at continental scales (Martiny et al, 2011). Moreover, their response to external nutrients has been recorded (Bowen et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…DGGE has been suggested as a good prescreening approach that could enhance and inform the application of next-generation sequencing (NGS) methods (Hanning & Ricke 2011). On the one hand, the resolution of DGGE was sufficient to reveal seasonal variation within the same lake; however, it is clear that deep sequencing of 16S rDNA gene fragments using NGS technologies would enable rare species to be better resolved (Bowen et al 2012). On the other hand, it is clear that current methods based on NGS technologies do not reveal the true diversity of complex microbial communities (Lundin et al 2012), and more robust methods should be applied to estimate the true richness of environmental communities (Haegeman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, we cannot measure what we cannot detect. The detection of rare taxa will have relatively high variability, not necessarily because they are ecologically more variable (though they may be) but because of challenges with consistent detection and making observations near the limits of measurement (Anders & Huber 2010, Dickie 2010, Reeder & Knight 2010, Bowen et al 2012, Lan et al 2012, Albertsen et al 2013, Haegeman et al 2013, Hugoni et al 2013, Delmont et al 2015. For example, rare members are often only present in either the rRNA gene pool or the rRNA pool but not both (İnceog lu et al 2015), suggesting a combination of technical detection limitation, high variability in activity/transcripts, and a large contribution of dormant taxa to the rRNA gene pool that collectively overwhelms signals from the rare biosphere.…”
Section: Detection Bias Against Rare Taxamentioning
confidence: 99%
“…along environmental gradients) are driven by true environmental constraints or are a byproduct of non-exhaustive or biased sampling efforts. A study in salt marsh sediment suggested that replicated detection of the rare biosphere can be consistent, at least for some habitats (Bowen et al 2012). Many of the rare biosphere members observed using cultivation-independent methods are presumed to be as yet uncultivable.…”
Section: Detection Bias Against Rare Taxamentioning
confidence: 99%